Shadowlands: A Search for the Unseen - Mok, Tori (Auckland University of Technology, 2019)
Beneath the quotidian world is a parallel universe of dim and shapeshifting forms. They are easy to overlook, difficult to see, and mesmerising to behold — like black holes collapsing, pulling into themselves an infinity of lost fragments. Here, on a journey to challenge the perceptual limitations of my habituated ways of seeing, I have searched for the unseen and discovered visual failure. This work is a collection of the strange curiosities and souvenirs I have unearthed in flipping my world over, hunting for darkness, and wandering through the Shadowlands.
Keywords: Shadow; Unseen; Visual perception; Curiosity cabinet; Photography; Quotidian; The everyday; Practice-based research; Perceptual failure; Fragment; Installation; Speculative design; Conceptual art; Optical device; Overhead projection